Antibacterial, cytotoxic and antioxidant potential of methanolic extract of phyllanthus acidus L - Rahman, Md. Mominur; Habib, Md. Razibul; Hasan, S. M. Raquibul; Rana, Md Sohel (© 2010 IJDDR, 2016)
This article was published in International Journal of Drug Development and Research [© 2010 IJDDR] and the definite version is available at: https://goo.gl/L9BR2r